Structural and functional canges of the human macula during acute exposure to high altitude - Fischer, Manuel Dominik; Schommer, Kai (PLOS ONE, 2012)
Background This study aimed to quantify structural and functional changes at the macula during acute exposure to high altitude and to assess their structure/function relationship. This work is related to the Tuebingen High Altitude Ophthalmology (THAO) study. Methodology/Principal Findings Spectral domain optical coherence tomography and microperimetry were used to quantify changes of central retinal structure and function in 14 healthy subjects during acute exposure to high altitude (4559 m). High-resolution volume scans and fundus-controlled microperimetry of the posterior pole were performed in addition to best-corrected visual acuity (BCVA) measurements and assessment of acute mountain sickness. Analysis of measurements at altitude vs. baseline revealed increased total retinal thickness (TRT) in all four outer ETDRS grid subfields during acute altitude exposure (TRTouter = 2.80±1.00 μm; mean change±95%CI). This change was inverted towards the inner four subfields (TRTinner = −1.89±0.97 μm) with significant reduction of TRT in the fovea (TRTfoveal = −6.62±0.90 μm) at altitude. BCVA revealed no significant difference compared to baseline (0.06±0.08 logMAR). Microperimetry showed stable mean sensitivity in all but the foveal subfield (MSfoveal = −1.12±0.68 dB). At baseline recordings before and >2 weeks after high altitude exposure, all subjects showed equal levels with no sign of persisting structural or functional sequels. Conclusions/Significance During acute exposure to high altitude central retinal thickness is subject to minor, yet statistically significant changes. These alterations describe a function of eccentricity with an increase in regions with relatively higher retinal nerve fiber content and vascular arcades. However, these changes did not correlate with measures of central retinal function or acute mountain sickness. For the first time a quantitative approach has been used to assess these changes during acute, non-acclimatized high altitude exposure.
Gesehen am 12.07.2019